Increasing AZA-Accredited Zoo and Aquarium Engagement in Conservation - Ripple, Kayla J.; Sandhaus, Estelle A.; Brown, Megan E.; Grow, Shelly (Frontiers in Environmental Science, 2021)
Conservation should be the higher purpose of any modern zoological facility and has consistently been a required element of accreditation by the Association of Zoos and Aquariums (AZA). Each year, AZA-accredited zoos and aquariums collectively commit considerable resources to conservation around the world, exceeding 150 million USD annually since 2011 and exceeding 231 million USD in 2019. Furthermore, with 195 million people visiting AZA-accredited zoos and aquariums each year, there is enormous opportunity to connect people to nature and engage them as agents of change. As AZA facilities continue to prioritize conservation-driven missions, their participation in field conservation has increased greatly. AZA SAFE: Saving Animals From Extinction (SAFE)Ⓡ was established in 2014 to encourage greater collaboration of AZA members and their field partners to save species. The SAFE framework is dedicated to species recovery and based on conservation best practices. SAFE species programs develop 3-year action plans that build on established recovery plans, evaluate impact, and combine AZA facilities and visitors to increase resources for research, public engagement, communications, and conservation funding. Here we share preliminary outcomes of the SAFE program as they relate to programmatic measures of success to determine whether the framework 1) is useful for the AZA membership as measured by engagement and participation, and 2) increases conservation activity on behalf of targeted species as measured by the number of facilities supporting a species’ conservation and financial investment. In this analysis we utilized data supported by the AZA Annual Report for Conservation and Science (ARCS) and to demonstrate benefits of the SAFE framework and provide insights into future strategies to enhance conservation impact.